2021
DOI: 10.1016/j.numecd.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of metabolic syndrome risk: A review of reviews and proposal for defining pre-metabolic syndrome status

Abstract: Aims: a) To analyze the relationship of known and emerging biomarkers/indicators for early risk identification of cardiometabolic health risk; b) to identify early risk markers to be used in both clinical and nonclinical settings; and c) to propose a definition of early risk identification in terms of pre-metabolic syndrome (PreMetSyn). Data synthesis: Pubmed/Medline, Web of Science, Embase, and Cochrane were searched for Systematic Reviews and Meta-analysis. Selected studies were evaluated, and relevant data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 110 publications
0
17
0
2
Order By: Relevance
“…It was confirmed that variables such as sex, age, income per capita, educational level, total energy intake, smoking and/or drinking status, residential area, and PA were key in developing strategies to prevent metabolic syndrome in different populations [ 40 , 72 ]. Similarly, interventions seeking to reduce energy content through reformulation or diminishing portion sizes in restaurants, cafes, and TA could potentially lead to a decrease in mean daily energy intake [ 23 , 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was confirmed that variables such as sex, age, income per capita, educational level, total energy intake, smoking and/or drinking status, residential area, and PA were key in developing strategies to prevent metabolic syndrome in different populations [ 40 , 72 ]. Similarly, interventions seeking to reduce energy content through reformulation or diminishing portion sizes in restaurants, cafes, and TA could potentially lead to a decrease in mean daily energy intake [ 23 , 28 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mets group in present study was defined as meeting at least two criteria including both pre-MetS and Mets status, because of the importance of preventive healthcare by early detection of MetS in the middle-aged population [ 33 ]. MetS group was diagnosed by the following five criteria given in the NCEP-ATP III guidelines [ 1 ]: 1) a waist circumference above the cut-off point for Koreans (≥90 cm for males and ≥ 85 cm for females); 2) systolic blood pressure ≥ 130 mmHg, diastolic blood pressure ≥ 85 mmHg, or taking medication for hypertension; 3) a triglyceride level of ≥150 mg/dL or taking medication for such lipid abnormalities; 4) low high-density lipoprotein-cholesterol level (< 40 mg/dL for males and < 50 mg/dL for females) or taking medication for such lipid abnormalities; 5) a fasting plasma glucose level of ≥100 mg/dL or taking medication for type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Early prediction of the risk of DM+MetS comorbidity is absolutely important for DM and MetS patient management as well as for CVD prevention, decelerating disease progression, and mortality [10,17]. However, due to the lack of established standard screening methods, the effectiveness and reliability of MetS screening in a DM patient are not convincing, and standards for MetS diagnosis are likely to vary substantially [13,[20][21][22]. In addition, MetS diagnosis and determination need measurements of different parameters at a time that needs sophisticated materials and are easily affected by different factors [13,20].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome and diabetes are pro-inflammatory and prothrombotic disorders characterized by alteration of platelet indices and increased platelet reactivity [23][24][25]. The evidence relates platelet activation (PLT) to MetS and DM [3,4,21,25], however, the tendency to use them in diagnosis is not yet fully evaluated in our context. Platelet indices such as mean platelet volume (MPV), platelet crits (PCT), and platelet distribution width (PDW) are the indicators of increased platelet activity [23,24] and have been identified as potential new biomarkers of disease severity and comorbidity [25].…”
Section: Introductionmentioning
confidence: 99%